Leishmania infantum asymptomatic infection in inflammatory bowel disease patients under anti-TNF therapy - Guillén, M. Carmen (Heliyon, 2020)
BACKGROUND: In recent years anti-TNF therapy has been associated with leishmaniasis in immunocompromised patients from endemic areas. Nevertheless, data on asymptomatic Leishmania infection in such patients is scarce. The aim of this study was to determine the prevalence of asymptomatic infection in inflammatory bowel disease (IBD) patients treated with TNF inhibitors living in an endemic area (Catalonia) and to follow up them to study how the infection evolved. METHODS: 192 IBD patients (143 Crohn's disease; 49 ulcerative colitis) from Catalonia (Spain), an area endemic for L. infantum, were recruited. Peripheral blood samples were collected and tested for anti-Leishmania antibodies by Western blotting (WB). Leishmania kinetoplast DNA was detected in peripheral blood mononuclear cells (PBMC) by a quantitative PCR. RESULTS: Serology was positive in 3.1% and Leishmania DNA was found in 8.8%, with a low parasitic load and humoral response. The prevalence was 10.9%, patients being considered infected if they tested positive by at least one of the techniques. Eight out of the 21 patients with asymptomatic leishmaniasis were monitored for 3–8 months after the first test. None of them showed an increased parasitemia or humoral response, or developed leishmaniasis during the follow-up period. CONCLUSION: The prevalence of Leishmania asymptomatic infection detected in our IBD cohort is similar to that found in healthy population in close endemic areas. Due to the short monitoring period, it is not possible to reach a conclusion about the risk of Leishmania reactivation from this study.